Small Business Tax Regimes - Coolidge, Jacqueline (World Bank, Washington, DC, 2016)
Simplified tax regimes for micro and small enterprises in developing countries are intended to facilitate voluntary tax compliance. However, survey evidence suggests that small business taxation based on simplified bookkeeping or turnover is sometimes perceived as too complex for microenterprises in countries with high illiteracy levels. Very simple fixed tax regimes not requiring any books or records tend to be overly popular but prone to abuse. System reforms will require more precise tailoring of the simplified regimes to their target beneficiaries, coupled with strong compliance management to detect and deter abuse. The overall objective of simplified taxation for micro and small enterprises (MSEs) in developing countries is generally to facilitate voluntary tax compliance and remove obstacles in moving toward business formalization and growth.